Megacryst suite from the Salpeterkop carbonatite complex, Sutherland, Northern Cape, South Africa: an in-depth geochemical study - Peel, Chad (Department of Geological Sciences, 2021)
Presented here are major and trace element, stable (oxygen and hydrogen) and radiogenic (Sr-Nd-Pb) isotope analyses for a Cr-poor megacryst suite from the Salpeterkop complex, South Africa. The clinopyroxene, amphibole, phlogopite and ilmenite megacrysts all appear to be cogenetic, and based on known mineral relationships and intergrowths from xenoliths in the complex, the apparent order of mineral crystallisation is as follows: phlogopite → ilmenite → amphibole → clinopyroxene. Megacrysts of amphibole and phlogopite exhibit δD and δ18O values that are aligned with these grains having crystallised from melt originating from the upper mantle. Additionally, the amphibole and phlogopite megacrysts appear have experienced dehydration styled degassing, possibly related to their exhumation. Calculated P-T conditions have the megacrysts crystallising in the lower crust, under conditions ranging from 1 to 1.5 GPa (35 to 45 km depth) and 1000 to 1250 ℃. Calculated REE melts in equilibrium with the megacryst as well as radiogenic isotope results suggest that the Salpeterkop ultramafic lamprophyres are genetically related the the SPKC megacryst suite, however, the calculated parent melt to the megacryst appears to have mixed with a HIMU component. These findings primarily affect higher Mg-number megacrysts, suggesting that this assimilation or mixing occurred during initial stages of crystallisation. Lower Mg-number megacrysts lack the variations noted in their more primitive counterparts and present more tightly defined trends. A model of formation for the megacryst suite of the Salpeterkop complex sees grains having crystallised from an SPKC ultramafic lamprophyre-like melt originating from sublithospheric/asthenospheric conditions. During ascension the melt episodically assimilates material with a HIMU signature. The high Mg-number megacryst population crystallises from this melt at lower crustal depths. Soon after assimilation halts the megacryst parent melt homogenises (or re-homogenises), with grains to crystallise from this melt forming the low-Mg megacryst population.